Microemulsion Based Nanostructures for Drug Delivery - Arredondo-Ochoa, Teresita; Silva-Martínez, Guillermo A. (Frontiers in Nanotechnology, 2022)
Most of the active pharmaceutical compounds are often prone to display low bioavailability and biological degradation represents an important drawback. Due to the above, the development of drug delivery system (DDS) that enables the introduction of a pharmaceutical compound through the body to achieve a therapeutic effect in a controlled manner, is an expanding application. Henceforth, new strategies have been developed to control several parameters considered essential for enhancing delivery of drugs. Nanostructure synthesis by microemulsions (ME), consist of enclosing a substance within a wall material at the nanoscale level, allowing to control the size and surface area of the resulting particle. This nanotechnology has shown the importance on targeted drug delivery to improve their stability by protecting a bioactive compound from an adverse environment, enhanced bioavailability as well as controlled release. Thus, a lower dose administration could be achieved by minimizing systemic side effects and decreasing toxicity. This review will focus on describing the different biocompatible nanostructures synthesized by ME as controlled DDS for therapeutic purposes.